Sickness presenteeism associated with influenza‐like illness in veterinarians working in New South Wales: Results of a state‐wide survey. Issue 6 (15th February 2022) - Pasfield, K; Gottlieb, T; Tartari, E; Ward, MP; Quain, A
Abstract : Background: Sickness presenteeism in the veterinary profession potentially jeopardises the wellbeing of veterinary team members and endangers quality of patient care. In veterinary team members with influenza‐like illness (ILI), sickness presenteeism poses a risk to the health and wellbeing of colleagues and clients, particularly in the context of the COVID‐19 pandemic. This study aimed to evaluate factors associated with sickness presenteeism in NSW registered veterinarians suffering from ILI, both before and since the beginning of the COVID‐19 pandemic. Methods: Veterinarians registered in NSW were invited to complete an anonymous online mixed‐methods survey between 31 March 2021 and 31 June 2021, regarding sickness presenteeism and absenteeism associated with ILI. The questionnaire was distributed through online and print newsletters of the Australian Veterinary Association NSW Branch and the NSW Veterinary Practitioners Board. Results: From a total of 122 participants, 81 veterinarians (66.4%) reported that they would attend work despite displaying symptoms of ILI. Most veterinarians would stay at home with a fever alone (n = 108, 88.5%), however, many would still attend work with a sore throat (n = 121, 99.2%) or a dry cough (n = 91, 74.6%). Sickness presenteeism was significantly associated with lack of staff to cover workers. Although sickness presenteeism remained common, participants reported that they were less likely to attend work with symptoms of ILI since the beginning of the COVID‐19 pandemic. Discussion: The data are discussed in relation to sickness presenteeism in healthcare workers. These findings underscore an urgent need for relief staff to decrease sickness presenteeism.